The Sundance Kid: Simulacrum of a Visit. (February 2016) - van Herk, Aritha
The Canadian west differed from the American west in its depiction and its disposition. This is most strongly evident in outlaw history and mythology. This article is an intertextual and ficto-critical speculation on the bandit known as the Sundance Kid. His representation in the 1969 film Butch Cassidy and the Sundance Kid is read in counterpoint to his brief sojourn in southern Alberta, Canada, in the early 1890s, as Harry Longabaugh, horse breaker. His historical trace, as evidenced by census documents and vernacular histories, is juxtaposed with his folkloric depiction, and unfolded through the eyes of a viewer both skeptical and entranced by the enactment of the outlaw's vanishing.